2009
DOI: 10.1089/acm.2009.0067
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Scan for the Sasang Constitution in a Korean Family Suggests Significant Linkage at Chromosomes 8q11.22–23 and 11q22.1–3

Abstract: The 8q11.22-23 and 11q22.1-3 regions were suggested as the candidate region for significant linkage to Sasang constitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…In a large family comprising 40 individuals (26 TE, 2 SY, 8 SE, and 4 unknown), 2 genetic loci, 8q11.22-23 and 11q22.1-3, were suggested to be significantly linked with SCM type 17 . Using the genome-wide association study (GWAS) and functional assessment via a text mining-based approach, constitution-associated genes have been identified, including 15 TE-associated, 17 SY-associated, and 12 SE-associated genes 18 .…”
Section: Sasang Constitutional Perspective and Scientific Evidencementioning
confidence: 99%
“…In a large family comprising 40 individuals (26 TE, 2 SY, 8 SE, and 4 unknown), 2 genetic loci, 8q11.22-23 and 11q22.1-3, were suggested to be significantly linked with SCM type 17 . Using the genome-wide association study (GWAS) and functional assessment via a text mining-based approach, constitution-associated genes have been identified, including 15 TE-associated, 17 SY-associated, and 12 SE-associated genes 18 .…”
Section: Sasang Constitutional Perspective and Scientific Evidencementioning
confidence: 99%
“…To overcome difficulties in traditional diagnosis and to establish an evidence-based diagnostic tool, we developed the Sasang constitution analysis tool (SCAT), 11 a system designed to provide objective information for determining the SC type. In addition to the SCAT, several genomic approaches have been used to identify the genetic loci or pathways responsible for different SC types 12, 13. Won et al 12 found a significant link between the constitution and chromosomes 8q11.22–23 and 11q22.1–3 based on a genome-wide scan of a Korean family.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the SCAT, several genomic approaches have been used to identify the genetic loci or pathways responsible for different SC types 12, 13. Won et al 12 found a significant link between the constitution and chromosomes 8q11.22–23 and 11q22.1–3 based on a genome-wide scan of a Korean family. Kim et al 13 not only performed a genome-wide association analysis but also analyzed the pathways involved in SC.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific evidence revealed that these four body types have distinct genetic bases9, 10, 11 and differ in physical appearance,12, 13 body composition, 14 temperament traits, 15 hormonal regulations,16, 17 and vulnerability to particular diseases patterns 18, 19, 20. In terms of thermoregulation, a few investigations suggested constitution-specific traits in skin structure,21, 22 sweating capacity,21, 23 and energy expenditure profile 24 …”
Section: Introductionmentioning
confidence: 99%